Perancangan Mesin Sentrifugal Decanter Pati Sagu - Dinny Indrian; Bagus Budiwantoro; Indra Djodikusumo (Politeknik Manufaktur Negeri Bangka Belitung, 2020)
Indonesia is a country that has the largest area of sago in the world. Sago processing is currently done manually so that the production capacity of sago that can be produced is still very low. Centrifugal decanter machine is a machine that functions to precipitate and separate sago starch in order to increase capacity and shorten production time in sago flour processing. This study was carried out by observing a sago factory in the Tanah Baru area, Bogor with the amount of wet starch that can be obtained in a day that is 800 kg. The design of this centrifugal machine is carried out using the Pahl and Beitz design method. This machine consists of six sub-assemblies consisting of the frame, the slurry unit, cover, bowl and scroll, the successor round unit, and the motor and support. Based on the design results, the construction of a centrifugal decanter machine with the ability to precipitate and separate sago starch with a capacity of 8.5 m3/ hour with a bowl diameter of 195 mm and a pool height of 10mm. The deposition process occurs with the centrifugal force in the bowl with a rotational speed of 3000 rpm which is driven by an electric motor with a capacity of 7.5 HP (5.5 kW). Separation of starch with liquid occurs due to the difference in the rotation of the resulting screw to the bowl of 33 rpm. The rotation mechanism on the scroll is produced by different electric motors with 3 HP (2.2 kW) power.